2015
DOI: 10.1111/edt.12190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cytotoxicity of a mineral trioxide aggregate‐based sealer with respect to macrophage activity

Abstract: Comparison of MTA and FLPX effects upon macrophages indicates that FLPX may impair macrophage activity and viability, while MTA seems to increase phagocytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…The presence of resin in other sealers containing MTA, such as MTA Fillapex (Angelus Indústria de Produtos Odontológicos S/A, Londrina, PR, Brazil), reduced cell survival rates (Braga et al . , Mestieri et al . , Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of resin in other sealers containing MTA, such as MTA Fillapex (Angelus Indústria de Produtos Odontológicos S/A, Londrina, PR, Brazil), reduced cell survival rates (Braga et al . , Mestieri et al . , Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
“…The composition of endodontic sealers plays an important role in their biocompatibility. The presence of resin in other sealers containing MTA, such as MTA Fillapex (Angelus Ind ustria de Produtos Odontol ogicos S/A, Londrina, PR, Brazil), reduced cell survival rates (Braga et al 2015, Mestieri et al 2015, Zhou et al 2015, whilst Endoseal MTA (EndoSeal, Maruchi, Seoul, Korea), a new sealer without resin, had lower cell viability than ProRoot (PMTA; Dentsply, Tulsa, OK, USA) (Lim et al 2015). Although Endoseal MTA is another type of MTA-based root canal sealer, the composition and particle size of different MTAs are not the same.…”
Section: Introductionmentioning
confidence: 99%
“…Paste B includes silicon dioxide, titanium dioxide, and base resin (pentaerythritol, rosinate, and toluene sulphonamide), and 13.2% set MTA particles as filler. The working time is 23 min, with a complete set time of approximately 2 h. Several properties of this root canal sealer, such as flow and viscosity [10, 11], dimensional change [11], material porosity [12, 13], sealing ability [11], radiopacity, electrical conductivity [14], antibacterial effect [15], biocompatibility [1620], cytotoxicity [19, 2123], and genotoxicity [24, 25], have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturers’, this MTA-based sealer creates integrated, excellent and perfect seal and provides high biological regeneration (21). However, more recent studies have shown conflicting results regarding this claim (21,22). …”
Section: Discussionmentioning
confidence: 99%